Specific Features of the Source Basisuse in Historical and Pedagogical Researches - Zolotukhina, Svitlana (Pedagogical Discourse, 2013)
The approaches of modern scientists to determining of the essence of the historical and pedagogical source and its role in the developing of high-quality scientific research of historical and pedagogical character have been defined in the article; the forms of representation of the historical and pedagogical source basis (primary, actualised, potential) have been reflected in the article; approaches to the source classification (according to the amount, content, ways of codification, origin, places of storing, ways of presenting) have been determined and described; specific features of the source base use in historical and pedagogical researches dealing with pedagogical issues (didactic, upbringing, administrative), personalities’heritage and their contribution to the development of the pedagogical science, problems of comparative pedagogy have been revealed in this article.